2013
DOI: 10.1016/j.sjpain.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Pain and other symptoms in patients with chronic benign paroxysmal positional vertigo (BPPV)

Abstract: (A) Any disorder of the central nervous system (CNS), (B) migraine, (C) active Ménière's disease, and (D) severe eye disorders. Symptom questionnaire ('yes or no' answers during a personal interview) and Dizziness Handicap Inventory (DHI) were used. Results We included 69 patients (20 males and 49 females) with a median age of 45 years (range 21-68 years). The median duration of the disease was five years and three months. The video-oculography confirmed BPPV in more than one semicircular canal in all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…Studies have found patients with dizziness to have physical impairments (Iglebekk, Tjell, & Borenstein, ; Kvale, Wilhelmsen, & Fiske, ). Our study showed that patients in the DO group had increased physical impairment, including decreased CROM, neck and shoulder flexibility and a lower PPT in the neck, compared with healthy controls, indicating that patients with only dizziness (and not neck pain) have reduced physical function, which is usually explained by avoidance behaviour due to fear or anxiety of movement (Godemann, Schabowska, Naetebusch, Heinz, & Strohle, ; Lahmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have found patients with dizziness to have physical impairments (Iglebekk, Tjell, & Borenstein, ; Kvale, Wilhelmsen, & Fiske, ). Our study showed that patients in the DO group had increased physical impairment, including decreased CROM, neck and shoulder flexibility and a lower PPT in the neck, compared with healthy controls, indicating that patients with only dizziness (and not neck pain) have reduced physical function, which is usually explained by avoidance behaviour due to fear or anxiety of movement (Godemann, Schabowska, Naetebusch, Heinz, & Strohle, ; Lahmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the DN group were more likely to report a rocking sensation. A rocking or floating sensation, although describing illusory movement, has previously been associated with chronic types of dizziness (Fife & Kalra, ; Iglebekk, Tjell, & Borenstein, ) rather than ongoing vestibular dysfunction. Patients in the ND group were less likely to report a spinning type of dizziness, compared with those in the DO group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dizziness is considered a common and challenging condition that is observed in primary care settings and has often been reported as one of the major symptoms associated with NSCNP (Wipperman, 2014; Iglebekk, Tjell & Borenstein, 2017). In addition, patients with NSCNP may suffer from cervicogenic dizziness with a frequency similar to patients who suffer from cervical spine degeneration and whiplash (Wrisley et al, 2000; Treleaven, Jull & Sterling, 2003; Kristjansson & Treleaven, 2009; Hain, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This fear of provoking dizziness and discomfort may also lead to an "en block" movement pattern. Some studies on persons with persistent dizziness have also reported musculoskeletal symptoms (8), like for instance postural disalignments (9) and musculoskeletal pain (10), particularly in the neck-shoulder area (10)(11)(12). Longterm consequences of such avoidance strategies may hamper compensation strategies and functional improvements, eventually leading to occupational disability (13).…”
Section: Introductionmentioning
confidence: 99%